Humoral response against COVID-19 in the population of western region of Poland - Siedlecka, Dominika; Ludziejewska, Aleksandra; Bielawska, Lena; Baszczuk, Aleksandra; Gawron, Marta; Danielewicz, Mikołaj; Wysocka, Ewa (Frontiers in Public Health, 2025)
BackgroundExposure to the SARS-CoV-2 activates two forms of active immunity: natural appearance after infection and vaccine induced immunity.MethodsWe have conducted a retrospective analysis the serum concentration of IgG antibodies against SARS-CoV-2 in the population of Poznan University Clinical Hospital (PH) and Miedzyrzecz Hospital (MH) from 2021 to 2023.ResultsIn the entire study population (n = 3,104), as well as in the PH (n = 1,746) and MH (n = 1,358) groups, no significant differences in age (p = 0.1455) or BAU/ml values (p = 0.7874) between women and men were found. Significant differences were observed between the 18–35 and 36–60 age subgroups compared to the >60 age subgroup in the entire study population (p = 0.0022; p = 0.0001) and the PH group (p = 0.0176; p = 0.0003). In the MH group, significant differences were seen between the 18–35 and 36–60 age subgroups (p = 0.0305), as well as between the 18–35 and >60 age subgroups (p = 0.0050). A positive correlation was found between the number of infections and the number of tests conducted in each study group (R = 0.59, p = 0.0016).ConclusionThe concentration of anti-SARS-CoV-2 IgG antibodies is significantly higher in individuals over 60 years old compared to those in the 18–35 and 36–60 age groups. The correlations between age and antibody levels were significant but weak, suggesting that age should not be considered the main factor in predicting the immune response after vaccination or COVID-19 infection. Both women and men presented a similar immune responses to SARS-CoV-2 during the pandemic. Additionally, the number of infections within a specific time period influenced the number of individuals tested for anti-SARS-CoV-2 antibodies.